Seasonal Theanine Accumulation and Related Gene Expression in the Roots and Leaf Buds of Tea Plants (Camellia Sinensis L.) - Li, Fang; Dong, Chunxia; Yang, Tianyuan; Ma, Jingzhen; Zhang, Shupei; Wei, Chaoling; Wan, Xiaochun; Zhang, Zhaoliang (Frontiers in Plant Science, 2019)
Theanine, a unique and abundant non-proteinogenic amino acid in tea, confers the umami taste and multiple health benefits of tea infusion. Its content in new tea shoots is dynamic in winter and spring. However, its seasonal accumulation pattern and the underlying regulation mechanism in tea plant, remain largely unknown. In this study, we measured the theanine contents in the roots and leaf buds of 13 tea cultivars, at 4 time points from winter to spring (Dec. 12, Mar. 1, Mar. 23, and Apr. 13). We found theanine highly accumulated in the roots to as high as ~6% dry weight. We further found theanine content in the roots kept constant or slightly decreased at Mar. 1 compared with that at Dec.12, but consistently increased at Mar. 23 and then decreased at Apr. 13, in all these 13 cultivars. In the leaf buds, theanine contents kept increase from Mar. 1 to Mar. 23, and then decreased at Apr. 13, in most of the 13 cultivars, and were probably both season- and developmental stage-dependent. The expression of theanine biosynthesis and amino acid transporter genes in the roots and buds at the 4 time points was then examined. The correlation analyses between the gene expression and theanine contents suggested the expression of theanine-biosynthesis genes was generally and negatively correlated with theanine contents; however, the expression of amino acid transporter genes including CsLHT was generally and positively correlated with theanine contents. Finally, we showed that CsLHT has theanine transport activity. Taken together, this study provided insights into the seasonal regulation of theanine biosynthesis and transport in tea plants during winter and spring.